Comparison of synthetic medium and wastewater used as dilution medium to design scalable microbial anodes: Application to food waste treatment. (June 2015) - Blanchet, Elise; Desmond, Elie; Erable, Benjamin; Bridier, Arnaud; Bouchez, Théodore; Bergel, Alain
Highlights: Bioanodes were designed by replacing synthetic medium by costless wastewater. Using wastewater ensured 50% of the current density obtained in synthetic medium. Bioanodes differed in biofilm structures and redox charge contents. Current densities were directly correlated to the enrichment in Geobacteraceae . Wastewater is a suitable medium to design bioanodes for food waste treatment. Abstract: The objective was to replace synthetic medium by wastewater as a strategy to design low-cost scalable bioanodes. The addition of activated sludge was necessary to form primary bioanodes that were then used as the inoculum to form the secondary bioanodes. Bioanodes formed in synthetic medium with acetate 10 mM provided current densities of 21.9 ± 2.1 A/m 2, while bioanodes formed in wastewater gave 10.3 ± 0.1 A/m 2 . The difference was explained in terms of biofilm structure, electrochemical kinetics and redox charge content of the biofilms. In both media, current densities were straightforwardly correlated with the biofilm enrichment in Geobacteraceae but, inside this family, Geobacter sulfurreducens and an uncultured Geobacter sp. were dominant in the synthetic medium, while growth of another Geobacter sp. was favoured in wastewater. Finally, the primary/secondary procedure succeeded in designing bioanodes to treat food wastes by using wastewater as dilution medium, with current densities of 7 ± 1.1 A/m 2 .